Harnessing hyperaccumulator (Brassica oleracea var. alboglabra) extract for green synthesis of nickel oxide nanoparticles: A prospective route for post-phytoremediation - Hamdan, Abd Mujahid; Maulida, Zahratul; Lubis, Syafrina Sari; Sardi, Arif; Reksamunandar, Rhyan Prayuddy; Nisah, Khairun; Malik, Jamaludin (Brawijaya University, 2024)
Even though phytoremediation is considered a green technology for remediating heavy metals, there are some problems with the application of this technology, particularly when it comes to managing the biomass that is used. So, processing biomass needs to be given a lot of attention. This study outlined the utilization of extracts obtained from the hyperaccumulator plant Brassica oleracea var. alboglabra to synthesize nickel oxide nanoparticles. Subsequently, the nanoparticle underwent testing to determine its suitability as an absorbent for heavy metals, specifically lead, as well as its efficacy as an antifungal agent against Fusarium sp. strain. The characterization of nickel oxide nanoparticles involved several measurements, such as scanning electron microscopy analysis, high- and low-resolution transmission electron microscopy, energy dispersive spectroscopy, X-ray diffraction, and hysteresis curve acquisition. The research findings indicate that the extract from hyperaccumulators can be utilized for the synthesis of NiO, which exhibits an absorption capacity exceeding 98% and serves as an efficient antifungal agent against Fusarium sp. pathogens. The approach utilized in this study not only prioritizes